2018
DOI: 10.5540/03.2018.006.01.0311
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Integer linear and Quadratic Programming Formulations for HA-Assignment Problems

Abstract: Abstract. Home-Away Assignment problems are naturally cast as quadratic programming models in binary variables. In this work we compare alternative formulations. First, we propose another formulation by manipulating their special structure to obtain versions with 1/4 of the original size. By linearizing the quadratic objective function, we get two more alternative models to be compared with the quadratic ones. Numerical experiments exhibit the characteristics of each model. Palavras-chave.Sport scheduling, HA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 8 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…In this section we offer some computational experiments to compare the different studied models. At first, we deal with integer quadratic models, comparing the full sized and reduced versions, in a preliminary experiment, in part published at [10]. A more robust experiment is reported at the second part, comparing SDP relaxations for the HA-Assignment problem.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In this section we offer some computational experiments to compare the different studied models. At first, we deal with integer quadratic models, comparing the full sized and reduced versions, in a preliminary experiment, in part published at [10]. A more robust experiment is reported at the second part, comparing SDP relaxations for the HA-Assignment problem.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The break minimization problem in an RRT has been studied by many researchers [16,18,20]. In particular, De Werra and Dominique [28] proved that the number of breaks in an RRT is more than 2n − 2, and the number of breaks in an MDRRT is more than 6n − 6.…”
Section: Previous Studiesmentioning
confidence: 99%
“…RRT, a DRRT, and an MDRRT. To solve this problem, constraint programming [17], integer programming [16,18], and an approximation algorithm [20] have been studied in the past. In recent years, Urdaneta et al [18] demonstrated, through numerical experiments that formulating the problem as an unconstrained quadratic integer programming problem and solving it using the mathematical optimization solver is superior to other formulations with constraints.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations